Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Yang Berdampak Pada Loyalitas Konsumen Di Mcdonald’s Cabang Cibubur, Jakarta - Ynry Purnamasari; Putu Nina Madiawati (Jurnal Studi Manajemen dan Bisnis, 2014)
McDonald's is a fast food restaurant which is good because of the initial formation of the already apply standard observation checklist such as quality, service, cleanliness, and value. However, the implementation of McDonald's consumers find the taste and poor service provided by the service provider. The purpose of this study was to determine the effect of service quality on customer satisfaction impact on customer loyalty.The variables used in this study is the quality of service (X) as the independent variable, customer satisfaction (Y) as a mediating variable, and customer loyalty (Z) as the dependent variable. Based on the results of the analysis and processing of data it is found that quality of service influence 71.68%, customer satisfaction influence 70.3%, and customer loyalty influence 66%. The partial influence the quality of service on customer satisfaction is 30.14%. Influence of customer satisfaction on consumer loyalty is 1.04%. Influence of service quality on customer loyalty is 8.58%. The influence of service quality and customer satisfaction on customer loyalty simultaneously is 12.11% and is influenced by other variables amounted to 87.89%.